Evaluación de la calidad de fibra de alpaca, con la aplicación de complejo de microminerales en la comunidad de Apagua - Pujilí - Sánchez Sevilla, Ana Nathaly (2015)
This research was made in the Cotopaxi province, Pujilí Canton, Pilalo Parish, Apagua Community; quality alpaca wool, with application of microminerals complex were evaluated; with the objectives to calculate diameter and strength, and measuring wool length huacaya alpaca, after application of microminerals complex. To analyze the design completely randomized (DCR) was used with factorial arrangement 3x2, with the factors Age (E) and Dose (D). I worked with 30 females alpacas, aged 1-3 years (E1) and 3-5 (E2), in which the micromineralscomplex was applied. dose 1ml (D1) for the treatment (T1), dose 1.5 ml (D2) for the treatment (T2) and no dose for the control treatment (T0); complex was administered at the beginning of the investigation (day 0), month (day 30), and two months (day 60).